Deep Brain Stimulation for Tourette’s Syndrome: The Case for Targeting the Thalamic Centromedian–Parafascicular Complex - Testini, Paola; Min, Hoon-Ki; Bashir, Asif; Lee, Kendall H. (Frontiers in Neurology, 2016)
Tourette syndrome is a neurologic condition characterized by both motor and phonic tics and is typically associated with psychiatric comorbidities, including obsessive-compulsive disorder/behavior and attention deficit hyperactivity disorder and can be psychologically and socially debilitating. It is considered a disorder of the cortico-striato-thalamo-cortical circuitry, as suggested by pathophysiology studies and therapeutic options. Among these, deep brain stimulation of the centromedian-parafascicular nuclear complex (CM-Pf) of the thalamus is emerging as a valuable treatment modality for patients affected by severe, treatment resistant TS. Here we review the most recent experimental evidence for the pivotal role of CM-Pf in the pathophysiology of Tourette syndrome, discuss potential mechanisms of action that may mediate the effects of CM-Pf deep brain stimulation in Tourette syndrome, and summarize its clinical efficacy.